Upaya Guru Sekolah Dasar dalam Menerapkan Unggah Ungguh Basa pada Mata Pelajaran Bahasa Jawa Kelas 3 SDN Beji 02 - Kartikasari, Dewi (Faculty of Teacher Training and Education of Undaris, 2025)
This research was conducted because in Javanese language learning in grade 3 of elementaryschool, many teachers still have difficulty finding the right way to apply “unggah ungguh basa” to students.Therefore, the formulation of the problem taken is how elementary school teachers' efforts in applying“unggah ungguh basa” in Javanese language subjects for grade 3 of SDN Beji 02, East Ungaran, SemarangRegency. The purpose of this study was to determine the forms of elementary school teachers' efforts inapplying “unggah ungguh basa” in Javanese language subjects for grade 3 of SDN Beji 02. This type ofresearch is qualitative descriptive research. The sources of research data are class teachers and students ofgrade 3 of SDN Beji 02 with research data in the form of observation results, interviews and documentationconducted by class teachers and students of grade 3 of SDN Beji 02. The analysis techniques used are datareduction, presentation and conclusion. After analyzing the data, the researcher found several researchresults as follows: 1) providing an explanation of knowledge about “unggah ungguh basa” in a fun way; 2)inviting students to get used to using Javanese according to “unggah ungguh basa” when communicatingdaily, especially in Javanese language learning; 3) Often conducting Q&A with students using politelanguage; 4) being a role model for students on how to behave well; 5) using Javanese as the language ofinstruction in Javanese language learning.Keywords: unggah ungguh basa, Javanese language, elementary school, teacher’s effort